The pharmacological mechanism of Chinese herbs effective in treating advanced ovarian cancer: Integrated meta-analysis and network pharmacology analysis - Yang, Ze; Wang, Xiang; Hong, Wei; Zhang, Shiyi; Yang, Yang; Xia, Yongliang; Yang, Ruiwen (Frontiers in Pharmacology, 2022)
Background: Advanced ovarian cancer(AOC) develops rapidly, increasing the difficulty of treatment. Traditional Chinese medicine(TCM) plays a significant role in the treatment of AOC. To explore the efficacy and safety of TCM in the treatment of AOC and its effective targets, we performed this article. Methods: The major databases were searched for randomized controlled trials of TCM for the treatment of AOC. A meta-analysis of the efficacy of Chinese herbs on AOC was conducted using RevMan5.4 software. Active compounds and target genes were acquired using the TCMSP database. The main targets of AOC were obtained through the Gencards, OMIM, TTD, and Drugbank databases. A protein-protein interaction network carried out in the String platform was used to select core genes. The Metascape platform was applied to achieve GO and KEGG Enrichment Analysis. Results: A total of 24 studies were included. Meta-analysis showed TCM group improved Overall Response Rate (OR=2.71; 95% CI= [2.14,3.44], Z=8.25, P<0.00001), Overall Survival (OR=2.93, 95% CI= [2.03, 4.24], Z=5.72, P<0.00001), and Progression-Free Survival (OR=5.36, 95% CI= [5.03, 5.69], Z=31.88, P<0.00001) of AOC patients, as well as can reduce lots of adverse events. 120 compounds, 246 herb target genes, and 1503 disease targets were extracted. The 10 most important components were Quercetin, Kaempferol, 7-Methoxy-2-methyl isoflavone, Formononetin, Isorhamnetin, Hederagenin, Stigmasterol, Luteolin, 7-O-methylisomucronulatol, and Calycosin. The 20 core targets were TP53, STAT3, JUN, AKT1, MAPK3, RELA, MAPK1, ESR1, IL6, FOS, MAPK14, TNF, CDKN1A, RB1, CCND1, EGFR, STAT1, MDM2, MAPK8 and CAV1. KEGG enrichment analysis showed that there were many pathways directly related to different types of tumors, like pathway in cancer, prostate cancer, etc. Conclusion: Our article revealed TCM was effective and safe against AOC and Chinese herbs exerted effects on AOC through multi-target, multi-component, and multi-pathway mechanism.